Thoracoscopic (video-assisted thoracoscopic surgery) pneumonectomy, technical details and literature review - Hennon, Mark W.; Demmy, Todd L. (Video-Assisted Thoracic Surgery; Vol 3 (April 2018): Video-Assisted Thoracic Surgery, 2018)
It is not known if the benefits of thoracoscopic approaches over thoracotomy for lobar and sublobar resection for early stage non-small cell lung carcinoma (NSCLC) are realized for patients undergoing more extensive lung resection such as pneumonectomy. Approaching whole lung resection by video-assisted thoracoscopic surgery (VATS) has remained less common, therefore little evidence exists regarding the potential advantages of performing pneumonectomy by VATS. Despite this, continued efforts to decrease surgical morbidity and mortality associated with pneumonectomy, along with increasing surgeon experience, have led to reports for VATS pneumonectomy from select centers. The following represents a description of the important technical aspects, as well as a review of pertinent literature, largely from case series and single institution experiences regarding thoracoscopic approaches to pneumonectomy.